Geoprocessamento aplicado a gestão de informações territoriais do município de Grossos-RN :estudo multitemporal do uso e ocupação do solo - Nascimento, Sergio Roberto Vital do (2004)
The present work was carried through in the Grossos city - RN and had as main objectives the elaboration of an physicist-ambient, socioeconomic survey and execution a multisecular evaluation of 11 years, between 1986 and 1996, using remote sensing products, to evaluate the modifications of the land use, aiming at the generation of an information database to implementation a geographical information system (GIS) to management the this city. For they had been in such a way raised given referring the two Demographic Censuses carried through by the IBGE (1991 and 2000) and compared, of this form was possible to the accomplishment of an evaluation on the demographic aspects (degree of urbanization, etária structure, educational level) and economic (income, habitation, vulnerability, human development). For the ambient physical survey the maps of the natural resources had been confectioned (simplified geology, hydrography, geomorphologi, veget covering, ground association, use and occupation), based in comments of field and orbital products of remote sensoriamento (images Spot-HRVIR, Landsat 5-TM and IKONOS - II), using itself of techniques of digital picture processing. The survey of these data and important in the identification of the potentialities and fragilities of found ecosystems, therefore allows an adequate planning of the partner-economic development by means of an efficient management. The project was part of a partnership between the Grossos city hall the municipal City hall of Grossos - RN and the Geoscience post-graduate program of the UFRN, more specifically the Geomatica laboratory LAGEOMA